Fabrication, microstructure, and optical properties of Tm:Y3ScAl4O12 laser ceramics. Issue 3 (11th November 2019) - Feng, Yagang; Toci, Guido; Patrizi, Barbara; Pirri, Angela; Hu, Zewang; Chen, Xiaopu; Wei, Jiabei; Pan, Hongming; Li, Xiaoying; Zhang, Xing; Su, Sha; Vannini, Matteo; et al.
Abstract: Transparent 4 at.% Tm:Y3 ScAl4 O12 (Tm:YSAG) laser ceramics were fabricated by solid‐state reaction combined with vacuum sintering method. The 4 at.% Tm:YSAG ceramic sample sintered at 1800°C for 30 hours possesses homogenous microstructure and excellent optical properties, showing a transmittance of 79.3% at 2000 nm. The absorption and emission spectra of the Tm:YSAG ceramics are studied and compared with those of 4 at.% Tm:Y3 Al5 O12 ceramics. The introduction of Sc 3+ greatly affects the energy levels of the Tm 3+, causing the disappearance and degeneration of some absorption and emission peaks in the middle infrared region. The laser performance of the 4 at.% Tm:YSAG ceramics is also tested in the Quasi‐continuous‐wave (QCW) mode by pumping with a 790 nm laser diode (LD). A maximum laser output power of 0.54 W with a slope efficiency of 4.8% is achieved, which is the first laser output for Tm:YSAG ceramics.